Desenvolvimento de uma célula solar fotoeletroquímica utilizando a mesoporfirina como sensibilizador orgânico - Esmeraldo, Felipe Sá (2013)
The study involving the development of photovoltaic solar cells has been a much commented subject on the past few years. The conversion of solar energy into electrical energy, with use of photovoltaic solar cells, has been done mostly through the use of semi conductive junction devices. But there have been some modifications about the materials used for the development of these cells; amongst these changes we can highlight the use of photo excitable dyes or sensitizers. In this work was used mesoporfirin, obtained from the liquid of the cashew nut, as the sensitizer in a photoelectrochemic solar cell. Initially, a glass used in microscopy received the application of a SnO2:F thin film through spray pyrolysis technique, thus presenting conductive properties. After that, a layer of TiO2:Ag was applied over the conductive glass to act as a support during the immersion in mesoporfirin solution. After thee adsorption of the dye by the TiO2:Ag layer, an electrolyte (I-/I3 -) was added and, in the end, the cell was closed using as counter electrode, a conductive glass containing a layer of carbon in its surface. The different samples of conductive glass presented electric resistance of 3,77 – 8,00 Ω/□ and transmittance around 60% with wave lengths of λ ≥ 600nm. The TiO2:Ag layer applied presented a 30 μm thickness. With the exposure to sun light an electric current of 60,5 μA and a tension of 20,7mV was verified